1990
DOI: 10.1017/s0954579400000663
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on early language development: The context of social risk

Abstract: The impact of environmental risk on toddlers' cognitive and linguistic development was investigated in a longitudinal study of 78 high-risk families. The risk factors examined were family social status, mother's psychosocial functioning, and quality of dyadic involvement at 1 year of age (including measures of mother-infant interaction and infant-mother attachment security). Child outcome measures included the Bayley MDI (at 24 months) and the Preschool Language Scale (at 36 months). The data indicate that dya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
72
1
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 80 publications
9
72
1
6
Order By: Relevance
“…Such a decline was observed previously for infants raised in low-income families and communities, independent of chemical exposures, 37,55,56 in part because toddlers from low-income homes have less access to developmentally stimulating environments and may be delayed in acquiring language and problem-solving skills. [57][58][59][60][61][62][63] Although children with low HOME scores did have significantly lower BSID-II scores in this study, there was no indication that the chlorpyrifos effects were either exacerbated or remediated by the quality of the home environment. The finding that a large proportion of children scored in the delayed range on the MDI, although consistent with other reports for similar populations, 64,65 is worrisome, especially because the MDI is often given more importance than the PDI.…”
contrasting
confidence: 55%
“…Such a decline was observed previously for infants raised in low-income families and communities, independent of chemical exposures, 37,55,56 in part because toddlers from low-income homes have less access to developmentally stimulating environments and may be delayed in acquiring language and problem-solving skills. [57][58][59][60][61][62][63] Although children with low HOME scores did have significantly lower BSID-II scores in this study, there was no indication that the chlorpyrifos effects were either exacerbated or remediated by the quality of the home environment. The finding that a large proportion of children scored in the delayed range on the MDI, although consistent with other reports for similar populations, 64,65 is worrisome, especially because the MDI is often given more importance than the PDI.…”
contrasting
confidence: 55%
“…Specifically, it has been argued that economic hardship and poverty can lead to harsher, less responsive parenting and in turn poorer cognitive outcomes for children (Conger et al, 1992), suggesting that the real causal mechanism is parenting. Data from recent studies have supported this family process model (Burchinal, Roberts, Zeisel, Hennon, & Hooper, 2006;Duncan, Brooks-Gunn, & Klebanov, 1994;Morisset, Barnard, Greenberg, Booth, & Spieker, 1990; NICHD ECCRN, 2005). These studies have found that cognitively stimulating parenting as measured by the Home Observation for Measurement of the Environment (HOME; Caldwell & Bradley, 1984) or maternal emotional sensitivity as measured during mother -child interactions partially or fully mediate relations between social risk factors (such as poverty) and children's early cognitive development in studies that primarily included families from small or large cities (Burchinal et al, 2006;Klebanov, Brooks-Gunn, McCarton, & McCormick, 1998;Krishnakumar & Black, 2002; Linver, BrooksGunn, & Kohen, 2002).…”
mentioning
confidence: 85%
“…SES predicted the complexity and diversity of syntactic structures children produced during motherchild interaction (Vasilyeva et al 2008, Huttenlocher et al 2010, as well as children's performance on standardized tests of grammatical development (Morisset et al 1990, Dollaghan et al 1999. Recent findings from a normative sample of preschool children tested on a computerized language assessment indicated that children from low-SES homes had syntax comprehension scores at age 5 that were not significantly different from children from higher-SES homes at age 3, revealing a gap of nearly 24 months on test items including wh-questions and embedded clauses (Hirsh-Pasek et al 2015b).…”
Section: Grammatical Developmentmentioning
confidence: 99%